Bridge to recovery in two cases of dilated cardiomyopathy after long-term mechanical circulatory support - Pacholewicz, Jerzy; Zakliczyński, Michał; Kowalik, Violetta; Nadziakiewicz, Paweł; Kowalski, Oskar; Kalarus, Zbigniew; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Ventricular assist devices (VADs) have become an established therapeutic option for patients with end-stage heart failure. Achieving the potential for recovery of native heart function using VADs is an established form of treatment in a selected group of patients with HF. We report two cases of VAD patients with different types of pump used for mechanical circulatory support, a continuous flow pump (HeartWare ® ) and a pulsatile pump (POLVAD MEV ® ), which allow regeneration of the native heart. Patients were qualified as INTERMACS level 3-4 for elective implantation of an LVAD. Implantations were performed without complications. The postoperative course was uncomplicated. In the HeartWare patient the follow-up was complicated by episodes of epistaxis and recurrent GIB as well as driveline infection. The follow-up of the LVAD MEV patient was uneventful. Recurrent GIB forced us to withdraw aspirin and warfarin therapy and maintain only clopidogrel. In mid-February 2013 the patient was admitted due to dysfunction of the centrifugal pump with a continuous low-flow alarm and increase power consumption. Under close monitoring of the patient a decision was made to stop the pump immediately and evaluate cardiac function. The serial echocardiography studies showed significant improvement in LVEF up to 45% and no significant valvular pathology. In February 2013 LVAD explant was performed by left thoracotomy without complications. At six-month follow-up the patient was in a good clinical condition, in NYHA class I/II, and on pharmacological treatment.